PENGARUH BUDAYA ORGANISASI, MOTIVASI KERJA, LINGKUNGAN KERJA DAN INSENTIF TERHADAP KINERJA PEGAWAI DENGAN KEPEMIMPINAN SEBAGAI VARIABEL INTERVENING DI BANK CIMB SEMARANG - Tampubolon, Lambok D.R. (Manajemen Bisnis Kompetensi, 2016)
ABSTRACTThis study takes the object at Bank CIMB Semarang using respondents are employees who work at the bank intended to determine employee performance and the factors that affect employee performance. The purpose of this study was to determine the influence of organizational culture, work motivation, work environment and incentives to employee performance with leadership as an intervening variable in Bank CIMB Semarang. Samples are partially or vice studied in the population. Sample collection techniques using the cenÃÂsus sampling is done to all regular employees who are still actively working at Bank CIMB Semarang as many as 73 people. Results of testing the first hypothesis which states that there is a positive influence of organizational culture on employee performance with leaderÃÂship as an intervening variable, accepted. Results of testing the second hypothesis which states that there is a positive influence between work motivation on employee performance with leadership as an intervening variable, accepted. Results of testing the third hypothesis which states that there is a positive influence between work environment to employee perÃÂformance with leadership as an intervening variable, accepted. Results of testing the fourth hypothesis which states that there is a positive influence between incentives to employee performance with leadership as an intervening variable, accepted. The fifth hypothesis test results stating that there is a positive influence between the leadership of the performance of employees, received. The suggestions can be submitted is Chairman of Bank needs to improve the culture in the organization to cultivate innovation employees to the companyÃ¢â¬â¢s progress, the culture of gift ideas that help solving problems in the company, working proÃÂcedures done well, the selection of hiring done selectively and the guarantee of the quality of work employees. Leaders need to increase the motivation of employees by providing a challenge to the employee in completing the work, the suggestions and new ideas from employees, the work carried out employees in accordance with the expectations of leaderÃÂship, lack of respect for employees who experienced employees trying to do a search of new things to help other employees and the existence of a good rapport with other employÃÂees. Leaders need to improve the working environment of employees by means of lighting conditions need to be considered, the cleanliness of the room needs to be maintained, the neatness of the rooms need to be considered, and the existence of good relations between employees and management. Bank leaders also need to consider reasonable incentives and provide additional bonuses, commissions and overtime pay in accordance with the workload of employees.Keywords: budaya organisasi, motivasi kerja, lingkungan kerja dan insentif terhadap kinerja pegawai dengan kepemimpinan